Optimalisasi Biaya Distribusi Bangunan PT CV SARI GUNUNG dengan Metode Transportasi - Febrian Putri, Alfina; Sasi Kirana, Ardhita; Putri Permata Sari, Berliana; Ayu Agustian, Shobariyah; Purwaningrum, Titis (Teewan Journal Solutions, 2025)
This study aims to analyze the efficiency of material distribution in a construction company using the North West Corner (NWC) method. As one of the methods in linear programming, NWC is used to solve transportation problems with a simple initial approach. The research was conducted by collecting distribution data from three main warehouses to four different project locations, including supply capacity and demand. The analysis results show that the NWC method provides a quick and reasonably efficient initial solution in determining material distribution patterns with minimum transportation costs. Although this initial solution is not yet optimal, the NWC method offers valuable insights for further evaluation. The study also identifies distribution challenges such as imbalanced warehouse capacity, distances between locations, and fluctuating demand. To improve efficiency, recommendations are proposed through further analysis using optimization methods such as the Stepping Stone or Modi method. This study is expected to assist construction companies in planning more effective distributions to support operational sustainability. The implementation of this method can also be applied in other sectors with similar distribution characteristics.